Towards 1997 and the reunification of Hong Kong with China : the views of Hong Kong women : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology at Massey University - Talbot, Anne Julie (Massey University, 1998)
On 1 July 1997 China will regain sovereignty over Hong Kong. To investigate this event, this exploratory study examined whether Chinese women in Hong Kong thought that the reunification of Hong Kong with China would bring about particular changes, and, if so, in which sectors of society change would be effected. The study also asked if the women viewed these changes as positive or negative, and whether various groups of women had different concerns. An effort was made to allow women to give their views in their own words so that this study could be their 'voice' about the social change that might occur in Hong Kong due to the process of decolonisation. The first phase of this research involved 164 Hong Kong Chinese women. A questionnaire was devised with three sections: Section A gathered demographic data, Section B consisted of open-ended questions about the change of sovereignty, and Section C used a Likert-type scale to gauge strength of feeling. In the second phase of the study, four women, representing different socio-economic groups, participated in unstructured interviews. The quantitative data from the questionnaire were analysed using crosstabulation, and content analysis done on the open-ended questions and unstructured interviews. The main findings were that most respondents thought that major changes would occur in Hong Kong because of the reunification; that change would occur in particular sectors of Hong Kong society (the structure and personnel of government, legal system, human rights and freedoms, education system, welfare system, and that there would be an increase in corruption); and that changes in these areas would adversely affect their lives. The study also showed that the large majority of the women (85%) held either negative or ambivalent views about the reunification and that more highly educated women, women with higher status jobs, women enjoying a higher income, were more likely to be negative towards the reunification. Conversely, less educated women, from lower status positions, tended to be more positive.
Some Chinese content throughout
Keywords: Women; Attitudes; Hong Kong (China) 20th century; Social conditions